Association between nutrition literacy and cognitive impairment among older adults in Bengbu, China - Cui, Yan; Hu, Xiaoting; Tian, Xi; Sun, Yuhui; Zhang, Bingyong; Liu, Huaqing (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive impairment is a major public health concern. Nutrition literacy (NL) is the capacity of an individual to make informed decisions about nutrition, which is reflected in their eating behaviors and ultimately affects their overall nutritional wellbeing. The association between NL and cognitive impairment is unclear.MethodsA cross-sectional study was conducted among individuals aged 60 years and above. NL was evaluated via the validated NL-12 scale, and cognitive impairment was identified via a simplified 30-item Chinese Mini-Mental State Examination scale. The association between NL and cognitive impairment was examined via binary logistic regression.ResultsOf the 1,344 study participants, 30.3% had cognitive impairment. Compared with those in the lowest NL quartile, individuals in the highest NL quartile had a lower likelihood of experiencing cognitive impairment [odds ratio (OR) = 0.12, 95% confidence interval (CI) = 0.07–0.20]. This relationship extends to the dimensions of knowledge, understanding, obtaining, interactive, and critical skills. Moreover, the negative association of NL in the Q4 group with cognitive impairment, compared with that in the corresponding Q1 group, was significant regardless of age, sex, exercise status, and socioeconomic status. This association, however, was only evident in older adults who exhibited healthy behavior. Additionally, health behavior significantly moderated the association between NL and cognitive impairment, with an interaction p value of 0.018.ConclusionHigher levels of NL were associated with lower odds of cognitive impairment in older adults, especially those exhibiting healthier behavior. This study underscores the importance of enhancing NL as a means to mitigate cognitive impairment in older adults. Future research should concentrate on examining interventions that synergize NL with healthy lifestyle practices, ensuring their seamless integration into the daily routines of older adults to address the challenges associated with cognitive impairment effectively.